Sustainable Milk Production: Application of the Hierarchical Analytical Process Towards a Regional Strategic Planning - Olveira, Max W.; Agostinho, Feni; Almeida, Cecília M.V.B.; Giannetti, Biagio F. (Journal of Environmental Accounting and Management, 2026)
Milk corresponds to 20% of the Brazilian agribusiness GDP and its production is concentrated at Minas Gerais State. Different milk production systems co-exist in this region, which results in different sustainability performance and call for a multi-criteria analysis to subsidize decisions towards a regional milk production planning. This work uses the Analytical Hierarchical Process (AHP) to hierarchize milk production systems as for their sustainability. A cluster analysis considering 92 milk producers identified five distinct production systems: G1, G2, G3, G4, and G5. Social, economic, and environmental indices are calculated and used in the AHP to prioritize sustainability according to the decision-maker’s egalitarian, or hierarchical, or individualist profiles. Results indicate that system G1 features higher priority degree (higher sustainability) for all three profiles compared to other systems assessed, reaching 27% for the egalitarian, 31% for the hierarchical, and 31% for the individualist profiles. The worst performances were fared by system G4 in the egalitarian (12%), and hierarchical (13%), and by system G3 in the individualist profile (10%). Numbers could be considered by decision makers in order to subsidize a strategic planning towards a sustainable regional milk production, whereby a given system could be politically, technologically, and economically prioritized in detriment of another. Notwithstanding, the objective approach discussed in defining criteria and their weights could be useful in future studies related to a hierarchization of sustainability of any production system in different regions.